Uni-directional coupling between tibiofemoral frontal and axial plane rotation supports valgus collapse mechanism of ACL injury. Issue 10 (16th July 2015) - Kiapour, Ata M.; Kiapour, Ali; Goel, Vijay K.; Quatman, Carmen E.; Wordeman, Samuel C.; Hewett, Timothy E.; Demetropoulos, Constantine K.
Abstract Despite general agreement on the effects of knee valgus and internal tibial rotation on anterior cruciate ligament (ACL) loading, compelling debate persists on the interrelationship between these rotations and how they contribute to the multi-planar ACL injury mechanism. This study investigates coupling between knee valgus and internal tibial rotation and their effects on ACL strain as a quantifiable measure of injury risk. Nineteen instrumented cadaveric legs were imaged and tested under a range of knee valgus and internal tibial torques. Posterior tibial slope and the medial tibial depth, along with changes in tibiofemoral kinematics and ACL strain, were quantified. Valgus torque significantly increased knee valgus rotation and ACL strain (p<0.020), yet generated minimal coupled internal tibial rotation (p=0.537). Applied internal tibial torque significantly increased internal tibial rotation and ACL strain and generated significant coupled knee valgus rotation (p<0.001 for all comparisons). Similar knee valgus rotations (7.3° vs 7.4°) and ACL strain levels (4.4% vs 4.9%) were observed under 50 Nm of valgus and 20 Nm of internal tibial torques, respectively. Coupled knee valgus rotation under 20 Nm of internal tibial torque was significantly correlated with internal tibial rotation, lateral and medial tibial slopes, and medial tibial depth (R2>0.30; p<0.020). These findings demonstrate uni-directional coupling between knee valgus and internal tibial rotation in a cadaveric model. Although both knee valgus and internal tibial torques contribute to increased ACL strain, knee valgus rotation has the ultimate impact on ACL strain regardless of loading mode.